Religious Coping Strategies For Nurses' Work Related Stress: A Scoping Review - Ika Nopa; L Meily Kurniawidjaja; Dadan Erwandi (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Stress was recognized internationally as a work hazard for nurses, but effective coping can prevent work stress. Religious coping is the type of emotional coping that is widely used by nurses. A compilation of studies related to the role of religious coping in nurses' work-related stress is still limited. The purpose of this scoping review is to determine the use of religious coping technique in nurses and its impact on stress. Methods: This scoping review was carried out following the PRISMA Statement recommendations checklist, Items for Systematic Reviews, and Meta-Analyses-Extension for Scoping Reviews (PRISMA-SCR). Databases for literature searching were SCOPUS, Springer Link, and Science Direct. The search strategy was (nurse or nursing) and (religious or spiritual) and coping and (job stress or work stress or occupational stress). Only original research articles, published within the last 10 years, in English or Indonesian, free full-text availability, and focusing on nurses' religious coping synthesized by the authors. Result: A total of 14 articles have been included in the review. 10 out of 11 articles stated that nurses used religious coping. 2 of 2 articles that analyzed the relationship between religiosity and distress stated there was a significant relationship. 2 of 3 articles that analyzed the relationship between religious coping and distress stated there was no significant relationship, and 1 article stated they were significantly related. Conclusion: Religious coping is an emotional coping method commonly used by nurses to reduce stress. Religiosity is a resource for preventing work stress in nurses. There are variations in the results of the relationship between religious coping and stress in nurses. Variations in results can be caused by the type of stressor, level of religiosity, and indicators of religiosity. Future research needs to analyze how the types of stressors and religiosity affect religious coping. Keyword: Nurse, Religious Coping, Work Stress